2010
DOI: 10.1016/j.bbi.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific social regulation of inflammatory responses and sickness behaviors

Abstract: In many mammals, the availability of familiar conspecifics in the home environment can affect immune function and morbidity. Numerous sex differences exist in immune responses, but whether the social environment impacts the immune system differently in males and females is not fully understood. This study examined behavioral and physiological responses to simulated bacterial infection in adult male and female Wistar rats housed either with 3 same-sex non-siblings (Group) or alone (Isolate). Rats were injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 87 publications
6
41
2
Order By: Relevance
“…In one experiment, the induction of cytokine-mediated inflammation led laboratory rats to spend more time in close contact with familiar cage-mates [88]. Analogous results have been observed in humans.…”
Section: (C) Sickness Behaviours Affect Sociality and Disease Spreadsupporting
confidence: 59%
“…In one experiment, the induction of cytokine-mediated inflammation led laboratory rats to spend more time in close contact with familiar cage-mates [88]. Analogous results have been observed in humans.…”
Section: (C) Sickness Behaviours Affect Sociality and Disease Spreadsupporting
confidence: 59%
“…Hence, in rats, in addition to reducing active social behavior with an unfamiliar conspecific, LPS can also lead to more huddling with familiar cagemates (Yee and Prendergast, 2010). Similarly, juvenile rhesus monkeys injected with low-dose LPS spent more time in close proximity with and clinging to a familiar cage-mate than did vehicle-injected controls (Willette et al, 2007).…”
Section: Effects Of Inflammation On Social Behavior In Animalsmentioning
confidence: 99%
“…In zebra finches, group-housing (versus housing in isolation) is associated with reduced expression of sickness behaviour without significant alteration of the inflammatory response as quantified by plasma IL-6 [45], which could be an indication that in certain social contexts animals have some motivation to conceal their sickness, for example, to maintain social status. In male rats, group-housing also attenuates LPS-induced sickness behaviours, whereas in females, group-housing exacerbates these behaviours relative to LPS-injected animals housed in isolation [46]. In an experiment using house finches (Haemorhous mexicanus), infection with the bacterium Mycoplasma gallisepticum caused individuals to become more submissive (i.e.…”
Section: (D) Agonistic Interactions: Territorial Intrusions and Sociamentioning
confidence: 99%
“…Weil et al [38] demonstrated that in mice, maternal aggression towards a virgin male intruder was not changed by an LPS injection at a dose sufficient to induce classical components of sickness behaviour (such as reduced food intake). Both of these experiments show that Taeniopygia guttata (zebra finch) decreased SB in males [45] Rattus novergicus (rat) decreased SB in males, increased in females [46] rspb.royalsocietypublishing.org Proc. R. Soc.…”
Section: (B) Parental Carementioning
confidence: 99%